1991
DOI: 10.1111/j.1744-7348.1991.tb05357.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimum plant densities for three semi‐leafless combining pea (Pisum sativum) cultivars under contrasting field conditions

Abstract: Yield and yield components of three semi-leafless pea (Pisum satiuum) cultivars, of contrasting seed type/growth habit, were assessed at target planting densities of 40 -140 plants/m* on nine sites over three years. Flat-topped parabolic/asymptotic yield/density relationships were obtained. The plant density required to maximise (p max) and optimise (p opt) yield differed between cultivars: Helka, small blue, p max 126 plants/m2, p opt 101 plants/m* ; Solara, large blue, p max 124 plants/m2,p opt 94 plants/m2;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
(1 reference statement)
2
9
0
Order By: Relevance
“…The effect of increasing plant density on reduction in branching was similar to previous studies. The present study found a reduction in branching of 0.0097 branches plant (1 plants m (2 , which is greater than that observed by Heath et al (1991) Significance of random effects calculated using the COVTEST option in the PROC MIXED of SAS Institute, Inc. *, **, ***Significant at the 0.05, 0.01, and 0.001 probability levels, respectively.…”
Section: Basal Branchingmentioning
confidence: 49%
See 2 more Smart Citations
“…The effect of increasing plant density on reduction in branching was similar to previous studies. The present study found a reduction in branching of 0.0097 branches plant (1 plants m (2 , which is greater than that observed by Heath et al (1991) Significance of random effects calculated using the COVTEST option in the PROC MIXED of SAS Institute, Inc. *, **, ***Significant at the 0.05, 0.01, and 0.001 probability levels, respectively.…”
Section: Basal Branchingmentioning
confidence: 49%
“…Although yield increases at plant populations higher than 88 plants m (2 have been observed (Moot and McNeil 1995), any yield advantage above 100 plants m (2 is unlikely to be profitable, due to additional seed costs (Heath et al 1991). Unfortunately, there have not been any economic analyses of seeding rate in pea for western Canada.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1999, for instance, a year with good weather for growth, when the seeding density was increased there was a trend towards increased yield up to 19 % (sig = 0.059). Heath et al (1991) found that near maximum yields were maintained between 70 -140 plants m -2 due to the ability of the seed pea crop to make compensatory increases in the number of pods per plant as sowing density declined. Spies et al (2010) found the optimum economic plant density for the seed pea cultivars was 50 to 84 plants m -2 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore seed density that produces the highest yield depends on growing conditions (Heath et al, 1991;Adisarwanto and Knight, 1997;Uzun and Açikgöz, 1998;Tawaha and Turk, 2004;Pageau et al, 2007;Baird et al, 2009). The sugar snap crop is harvested in the green pod phase with a degree of maturity that must be set based on crop morphological characteristics.…”
Section: Introductionmentioning
confidence: 99%